Advanced applications of tunable ferrofluids in energy systems and energy harvesters: A critical review. (1st October 2017) - Khairul, M.A.; Doroodchi, Elham; Azizian, Reza; Moghtaderi, Behdad
Highlights: Current developments in ferrofluids are reviewed. The effects of unique features of ferrofluids on thermal properties are studied. Applications of tunable magnetic nanofluids in energy harvesters are discussed. Future research on ferrofluid based electromagnetic energy harvesters are suggested. Abstract: Ferrofluids or Magnetic nanofluids (MNFs) are the suspensions of magnetic nanoparticles and non-magnetic base fluid. The heat transfer performance of a magnetic nano-suspension is influenced by the strength and orientation of an applied magnetic field. The main attraction of these types of nanofluids is that they not only enhance the fluids' thermophysical properties but also possess both magnetic characteristics like the other magnetic materials and flow ability similar to any other fluids. Such an exclusive feature enables to control heat transfer, fluid flow and movement of the nanoparticles by using the external magnetic fields. This review paper summarises the recent investigations of magnetic nanofluids with the aim of identifying the effects of major parameters on the performance of heat transfer. In addition, this study also acknowledged the novel application of ferrofluids in the electromagnetic energy harvesters, and its challenges as well as the potentiality in the future research.